2014
DOI: 10.1002/art.38399
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate Has Proapoptotic and Proinflammatory Effects on Articular Cartilage and Synergizes With Interleukin‐1

Abstract: Objectives Obesity is a major risk factor for the development of osteoarthritis (OA) that is associated with a state of low-grade inflammation, and increased circulating adipokines and free fatty acids (FFA). The aim of this study was to analyze effects of saturated (palmitate) and monounsaturated (oleate) free fatty acids (FFA) on articular chondrocytes and cartilage. Methods Human articular chondrocytes and fibroblast-like synoviocytes obtained from young healthy donors, and OA chondrocytes from patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 46 publications
6
64
1
1
Order By: Relevance
“…Indeed, type 2 DM is characterized by hyperglycemia, hyperinsulinemia with insulin resistance and free fatty acids increase 45,46 . Some studies have examined the role of insulin in joint tissues and have shown an anabolic role of this hormone with the induction of the synthesis of type II collagen and proteoglycans by chondrocytes 47e49 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, type 2 DM is characterized by hyperglycemia, hyperinsulinemia with insulin resistance and free fatty acids increase 45,46 . Some studies have examined the role of insulin in joint tissues and have shown an anabolic role of this hormone with the induction of the synthesis of type II collagen and proteoglycans by chondrocytes 47e49 .…”
Section: Discussionmentioning
confidence: 99%
“…Au genou, il est possible que les adipokines secrétées par le tissu graisseux de Hoffa diffusent jusque dans l'articulation de voisinage [25]. À côté des adipokines, on a observé aussi le rôle d'autres facteurs, tels que certains acides gras libres saturés comme le palmitate qui ont in vitro un effet pro-inflammatoire, prodégradatif et pro-apoptotique sur les chondrocytes [26].…”
Section: Le Stress Systémique Et Métabolique Pour Expliquer L'arthrosunclassified
“…They also play a key role in various chronic diseases such as diabetes and atherosclerosis [118,159]. It has also been recently found that 'palmitic acid exerts proapoptotic and pro-inflammatory' actions in the articular cartilage, acting in conjunction with IL-1β to facilitate chondrocyte death and cartilage destruction [153]. Wu C.L et al compared a low-fat diet and an SFA diet for wound healing properties and concluded that SFA significantly worsened OA [121].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In obesity-related OA, the SFA attract a huge interest due to their increased expression compared to other free fatty acids [153]. Dietary SFA has been known to decrease 'membrane fluidity' in the cells which in turn triggers a cascade of metabolic pathways.…”
Section: Shining the Spotlight On Sfa And Oamentioning
confidence: 99%
See 1 more Smart Citation